Implementasi Ius Contra Legem oleh Hakim terhadap Tindak Pidana Pencabulan Anak yang Berdasarkan Nilai Keadilan - Abdul Malik Mufty; Nur Sri Maryam DM (Pusat Riset dan Inovasi Nasional, 2025)
Judges are always faced with concrete events, conflicts or cases that must be resolved or resolved and for this reason the law needs to be found. Right against the law is a legal principle that allows judges to override norms in statutory regulations because the relevant statutory regulations are not in accordance with the values ​​of justice and social conditions of society on condition that they must be based on rational legal arguments. Example of a judge's decision that applies right against the law namely SAS who was sentenced to death for committing sexual abuse and rape against children. This research uses normative juridical research with secondary data support. The results of this research are that a judge, in examining, adjudicating and deciding a case before him, must first use written law, but if the written law according to the judge's belief does not produce justice and truth, then the judge can implement it. right against the law Judges in handling cases of sexual abuse and rape against children can apply the death penalty to the perpetrator right against the law namely overriding norms in statutory regulations because the relevant statutory regulations are not in accordance with the values ​​of justice and the social conditions of society.